Paradigma Pendidikan Karakter Menurut Pemikiran Imam Al-Ghazali dalam Kitab Bidāyatul Hidāyah - Siti Maemunah Rohmah; Tajudin Noor; Undang Ruslan W (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2021)
Education as a forum for the development of human potential has a noble goal, namely to form a generation with character and decorated with noble morals. The current condition is attracting attention regarding moral decadence in the midst of public life. Therefore, the assessment and implementation of character education is needed in order to alleviate increasingly crucial educational problems. This study aims to determine how the paradigm of character education according to Imam Al-Ghazali in the Bidayatul Hidayah book. The research method used is the library research method, the opinion of experts about the paradigm of the character education of Imam Al-Ghazali in the book Bidayatul Hidayah. In his efforts to overcome moral problems, Imam Al-Gahzali focused on moral formation. This can be seen from his various works, one of which is the book Bidayatul Hidayah. In this book, the paradigm of character education according to Imam Al-Ghazali includes straight intentions in studying, carrying out obedience as best as possible. As well as displaying good ethics in socializing. This shows that Imam Al-Ghazali is very concerned in alleviating the problem of moral decadence. There for it is very appropriate if his work is used as a reference in the development of character education. Pendidikan sebagai wadah pengembangan potensi manusia memiliki tujuan mulia yakni membentuk generasi yang berkarakter dan di hiasi akhlak mulia. Kondisi saat ini menyita perhatian seputar dekadensi moral ditengah kehidupan masayrakat. Maka dari itu pengkajian dan pelaksanakan pendidikan karakter sangat diperlukan guna mengentaskan masalah pendidikan yanng semakin krusial. Penelitian ini bertujuan untuk mengetahui bagaimana paradigma pendidikan karakter menurut Imam Al-Ghazali dalam kitab Bidayatul Hidayah. Metode penelitian yang digunakan adalah metode library research, pendapat para ahli tentang paradigma pendididkan karakter Imam Al-Ghazali dalam kitab Bidayatul Hidayah. Dalam upayanya mengatasi permasalahan moral Imam Al-Gahzali memfokuskan pada pembentukan akhlak. Hal tersebut dapat dilihat dari berbagai karyanya salah satunya adalah kitab Bidayatul Hidayah. Dalam kitab ini dijelasakan paradigma pendidikan karakter menurut Imam Al-Ghazali yang meliputi niat lurus dalam menuntut ilmu, melaksanakan ketaatan dengan sebaik mungkin. Serta menampilakn etika yang baik dalam bergaul. Hal ini menunjukan bahwa Imam Al-Ghazali sangat konsen dalam mengentaskan permasalahan dekadensi moral. maka dari itu sangat tepat jika karyanya dijadikan rujukan dalam pengembangan pendidikan karakter.